Cost-price relationships in a concentrated economy - Falk Bräuning; José Luis Fillat Comenge; Gustavo Joaquim (Federal Reserve Bank of Boston, 2023)
We use local projections with granular instrumental variables to estimate the aggregate pass-through of costs into prices and how it is affected by industry concentration. On average, we find, prices increase above trend growth for three quarters after an exogenous cost shock, and the price increase is accompanied by a decline in output. The estimated pass-through of the shock into prices one quarter ahead is 0.7. The price response to shocks becomes about 27 percent larger when there is an increase in concentration similar to the one observed over the last 20 years. This differential effect depending on concentration is primarily driven by a larger pass-through of positive shocks that increase costs. Consistent with a market power channel, margins decrease less in more concentrated industries after cost increases. Within industries, margins of industry leaders are not squeezed in response to positive cost shocks, unlike those of followers, while negative shocks increase margins for all firms. Our findings shed light on the post-COVID inflationary pressures and the linkages between inflation dynamics and rising market concentration.
Keywords: E30; E31; L11; L16; 330; cost-price pass-through; industry concentration; inflation; supply shock identification